Laser Ablation of Benign Thyroid Nodules: A Prospective Pilot Study With a Preliminary Analysis of the Employed Energy - Costa de Freitas, Ricardo Miguel; Miazaki, Aline Paterno; Tsunemi, Miriam Harumi [UNESP]; Furtado de Araujo Filho, Vergilius Jose; Marui, Suemi; Seguro Danilovic, Debora Lucia; Buchpiguel, Carlos Alberto; Chammas, Maria Cristina (Wiley-Blackwell, 2019)
Background and Objectives To assess the effectiveness of ultrasound (US)-guided laser ablation of benign thyroid nodules (TNs) under different amounts of applied energy. Study Design/Materials and Methods Thirty-four euthyroid patients with 5-18 ml TNs were enrolled: 21 (laser ablation) and 13 (clinical follow up) patients with a mean age of 56.2 +/- 12.0 and 54.7 +/- 14.7 years, respectively. The laser ablation protocol used a 1.064 mm wavelength diode laser source; 3.5 W output power; 1,100-1,500 J and 5-8 min/illumination; and one or two fibers/session. Clinical, laboratory, and US data were obtained immediately before treatment and at 6 and 12 months follow-up and were analyzed by Student's t test and Fisher's exact test. Low- and high-energy subgroups were subsequently defined, and the receiver operating characteristic (ROC) curves were calculated. Results Laser ablation follow-up showed an overall nodule volume reduction of more than 50%; improvement of symptoms and cosmetic complaints (P = 0.001); and stable laboratory data compared with the baseline and control groups. Minor complications were 9.5% (n = 2). One or two fibers/session resulted in a similar nodule volume reduction among 10-18 ml nodules. Analysis of the applied energy suggested a 398.8 J/ml inferior cutoff (ROC curve: 0.889 sensitivity; 0.545 specificity) for the high-energy subgroup (n = 14, mean 599.9 +/- 136.5 J/ml) to reduce the nodule volume over time (-55.1% vs. -58.4%, P = 0.55). The low-energy subgroup (n = 7, mean 240.2 +/- 74.6 J/ml) did not show a persistent volume reduction (P < 0.05) from the 6- to 12-month follow-ups (-56.6% vs. -53.7%). Conclusions Laser ablation of benign TNs achieved technique efficacy at 12 months posttreatment, with clinical improvement and few minor side effects. A single fiber in a single session with a high deployed energy (>398.8 J/ml) may be associated with improved results, a finding to be confirmed with a larger series. Lasers Surg. Med. (c) 2019 Wiley Periodicals, Inc.
Keywords: thyroid nodule; ultrasonography; interventional; laser therapy; ablation techniques; hyperthermia; induced